Central Bank Objectives On The Axis of Growth-Degrowth Debates: Case Of The European Central Bank From A Human Rights Perspective - Onat Kilic,Arinc (2021)
This thesis focuses on the correlation between the secondary objectives of the European Central Bank (ECB) and the right to a healthy environment. Whereas the primary mandate of the ECB is to maintain price stability, the applicable law also envisages secondary objectives, such as supporting economic growth and sustainable development. In parallel, the ECB continues to support the fossil fuel industry within its quantitative easing and collateral frameworks. Crucially, however, emerging degrowth theory indicates that there is a fundamental contradiction between the ECB’s secondary objectives, on the one hand, and sustainable development and economic growth on the other. In other words, environmental protection and economic growth cannot go hand in hand. This leaves the ECB with a legal dilemma. Should the ECB support environmental protection and sustainability, or economic growth? This thesis aims to analyse the given dilemma with a specific focus on legal implications in terms of the right to a healthy environment. This study, ultimately, reveals the failure of the Member States to comply with the requirements of the right to a healthy environment in shaping the law of the ECB. This is because the legal frameworks underlying the ECB’s operation have been designed in a way that the overall monetary policy will ultimately contribute to economic growth, rather than supporting the transition to a sustainable economy. Indeed, it appears that the Union’s free-market economy and its governing law prioritize economic growth over sustainability. Thus, revisions to the legal frameworks would have structural limitations in realizing the right to a healthy environment.
Keywords: ECB; central bank; right to a healthy environment; sustainable finance; climate finance